PERANAN DESA PAKRAMAN DALAM PENYELENGGARAAN OTONOMI PEMERINTAHAN DESA - Puja Sukmiwati, Ni Putu; Sudiarta, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
Pakraman village as the unity of indigenous peoples has important role to support the local governments in the implementation, operation and development in all sectors based on the spirit of regional autonomy. In the role of the Pakraman village , it shows that the Pakraman Village has exclusivity compared to the position and role of Administrative Village. Therefore, this paper will explain the role of Pakraman Village in the implementation of the autonomy of the village governance, hence concerning the rolling of the Village’s government by the Prakaman Village, the position and the authority of Pakraman Village in the sense of Village governance. This research uses normative legal method. Based on the yuridis aspect the authority of the Pakraman Village is similar with the Administrative Village, but the Pakraman Village also holds the role in the sociological aspect the Pakraman Village has to implement the social agendas and also religious activities to support the implementation of village governance.
Keywords: Role, Pakraman Village, Autonomy, village governace